Capital Structure and Regulation: Does Ownership Matter? - Carlo Cambini; Bernardo Bortolotti; Laura Rondi; Yossi Spiegel (Fondazione Eni Enrico Mattei (FEEM), 2007)
We construct a comprehensive panel data of 96 publicly traded European utilities over the period 1994-2005 in order to study the relationship between the capital structure of regulated firms, regulated prices, and investments, and examine if and how this interaction is affected by ownership structure. We show that firms in our sample increase their leverage after becoming regulated by an independent regulatory agency, but only if they are privately controlled. Moreover, we find that the leverage of these firms has a positive and significant effect on regulated prices, but not vice versa, and it also has a positive and significant effect on their investment levels. Our results are consistent with the theory that privately-controlled firms use leverage strategically to shield themselves against regulatory opportunism.
Keywords: L51; G31; G32; L33; 330; Regulated Utilities; Regulatory Agencies; Capital Structure; Leverage; Investment; Private and State Ownership; Kapitalstruktur; Versorgungswirtschaft; Regulierung; Eigentümerstruktur; Öffentliches Unternehmen; Privatisierung; EU-Staaten